2005
DOI: 10.1093/hmg/ddi382
|View full text |Cite
|
Sign up to set email alerts
|

Two single-nucleotide polymorphisms in the human vitamin D receptor promoter change protein–DNA complex formation and are associated with height and vitamin D status in adolescent girls

Abstract: Numerous association studies have dealt with single-nucleotide polymorphisms (SNPs) in coding and intronic regions of the human vitamin D receptor (hVDR) gene. We have hypothesized that phenotypic traits may also be associated with variations in VDR expression due to the presence of SNPs in promoter regions. In this work, we have studied two SNPs located 1521 bp (G/C) and 1012 bp (A/G) upstream of the transcriptional start site of the main human VDR gene promoter. One base-change in any of the two variant site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 45 publications
0
63
2
1
Order By: Relevance
“…We have shown in gel shift assays that GATA-3 binds preferentially to the A allele of A-1012G (unpublished results) and d'Alesio et al 9 and Fang et al 10 have also shown that GATA binding occurs preferentially at the A allele. Both also showed increased promoter activity of the A allele of A-1012G in reporter assays.…”
Section: Discussionmentioning
confidence: 59%
“…We have shown in gel shift assays that GATA-3 binds preferentially to the A allele of A-1012G (unpublished results) and d'Alesio et al 9 and Fang et al 10 have also shown that GATA binding occurs preferentially at the A allele. Both also showed increased promoter activity of the A allele of A-1012G in reporter assays.…”
Section: Discussionmentioning
confidence: 59%
“…This concept may be indirectly supported by positive associations that have been observed between height and pancreatic cancer by others (30,31), as well as in this nestedcase control study. Vitamin D receptor polymorphisms have been associated with adult stature (32)(33)(34) and adult height may be a marker for exposure to growth factors during childhood and adolescence. Alternatively, vitamin D status could be correlated to unmeasured exposures that may increase pancreatic cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…We selected polymorphisms that have been reported to be associated with serum 25(OH)D levels in either GWAS or candidate gene studies [8,9,11,12,[15][16][17][18][19][20]. Well-known VDR polymorphisms reported to be associated with bone mineral density and several vitamin D-related diseases were also included [21][22][23].…”
Section: Gene Analysismentioning
confidence: 99%